Antioxidant and Cytotoxic activity of Steroidal Alkaloids Isolated from Sarcococca saligna against DPPH and HeLa Cell Lines - Jan, Naeem Ullah; Kifayatullah, Muhammad; Amin, Fazli; Rahim, Haroon; Abbas, Sudhair; Mohani, Syed Nadeem Ul Hassan; Aman, Salman; Raza, Muslim (Indian Journal of Pharmaceutical Education and Research, 2022)
Background and Objectives: Cancer is believed to be one of the main challenges to health care profession and compounds isolated from natural products play significant role in treatment of cancer. Sarcococca saligna (Buxaceae) contains variety of steroidal alkaloids having numerous pharmacological and biological potentials. Hence, current research work was designed to isolate steroidal alkaloids from Sarcococca saligna and to evaluate it for antioxidant and cytotoxic activity. Materials and Methods: Compounds Alkaloid-C, Dictyophlebine, Sarcovagine-D and Holaphylline were purified by column chromatography followed by spectroscopic techniques for their structure confirmation. Antioxidant and cytotoxic activities were investigated against DPPH and HeLa cell lines using ascorbic acid and doxorubicin as standard. Results: The radical scavenging effect produced by Holaphylline and Sarcovagine-D was 80.0±3.20 and 78.0±3.20 % at 400 μg/ml concentration which was statistically similar to that of standard, while on the same concentration inhibition for Dictyophlebine and Alkaloid-C was 10.0±0.00% and 20±1.01 %. In addition, Holaphylline showed less anticancer activity (23.88±0.243) in cell growth of HeLa cell followed by Alkaloid-C (12.9±0.235), Dictyophlebine (6.1±0.345), while S cytotoxic effect for Sarcovagine-D was high (5.1±0.14) in (IC50), which exhibiting statistical variation from Doxorubicin (2.1±0.14%). Conclusion: This study provided scientific report and importance of the use of steroidal alkaloids from Sarcococca saligna as an antioxidant and cytotoxic against agents’ HeLa cell lines that may provide a new scope toward the development of novel drugs for cancer remedy.
Keywords: Sarcococca saligna; Alkaloid-C; Dictyophlebine; Sarcovagine-D; Holaphylline; Doxorubicin; IC50